1999
DOI: 10.1039/a901503e
|View full text |Cite
|
Sign up to set email alerts
|

Composition of sodium taurocholate micellar solutions

Abstract: The composition and range of existence of aggregates formed by sodium taurocholate in aqueous micellar solutions were studied. Electromotive force measurements were used to obtain concentrations of free hydrogen and sodium ions. Experimental data obtained at 25 degrees C and at three N(CH3)(4)Cl concentrations, used as anionic medium, can be explained by assuming the presence of aggregates with different compositions depending on the reagent concentrations and the ionic strength. Comparison with taurodeoxychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…The same gel formation is favoured by high bile salt and hydrogen ion concentration. This conclusion agrees well with experiments carried out in previous researches 12,13 . The gel formation takes place more easily in TDC than in TC solutions.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The same gel formation is favoured by high bile salt and hydrogen ion concentration. This conclusion agrees well with experiments carried out in previous researches 12,13 . The gel formation takes place more easily in TDC than in TC solutions.…”
Section: Resultssupporting
confidence: 94%
“…From the protonation constants of the two investigated bile salts, it can be deduced that their protonation to form the corresponding acid takes place only at high hydrogen ion concentration (-log c H ≤ 2). Previously, it was found that the formation of protonated micellar species started at lower c H both for TDC (-log c H ≤ 7.5) and for TC (-log c H ≤ 4), respectively 12,13 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…measurements as a function of hydrogen ion and reagent concentration. [6][7][8][9][10][11] Reagent activity coefficients were kept constant, in spite of a wide change of concentrations, adopting the constant ionic medium method. 12 N(CH 3 ) 4 Cl at different concentrations was selected as an ionic medium considered inert.…”
Section: Introductionmentioning
confidence: 99%
“…In the investigations on the dihydroxycholanic salts, 6-8 W was 0.100, 0.200, 0.300, 0.400, 0.500, 0.600 and 0.750 mol dm -3 , while in the case of the trihydroxycholanic salts [9][10][11] , W was only 0.100, 0.500 and 0.800 mol dm -3 .…”
Section: Introductionmentioning
confidence: 99%